The Influence of Mother Tongue Transfer on Second Language Acquisition and Its Countermeasures - Huang, Wenqi (Transactions on Social Science, Education and Humanities Research, 2024)
With the deepening of globalization and the deepening of communication between different countries and regions, people’s demand for learning a second language has become stronger and stronger, and second language acquisition has gradually entered the public’s vision. However, in the process of learning, learners will inevitably be influenced by their mother tongue to varying degrees. This phenomenon is known in psychology as "mother tongue transfer". In the field of linguistics, "mother tongue transfer" usually refers to the application of the forms and rules of the mother tongue to second language acquisition, which will have an important impact on the outcome of second language acquisition. In order to help second language learners further their second language learning and second language educators carry out their work better, this paper analyzes the positive and negative effects of mother tongue transfer on second language acquisition from four aspects: phonetics, vocabulary, grammar and culture and gives reasonable suggestions.